(untitled) (Research, Society and Development, 2021)
Encelopathies are constituted by a group of heterogeneous etiologies, having a clinical condition that needs rapid attention to be identified. Among the encelopathies, some have been more studied in recent decades, such as Hashimoto’s Encephalopathy (HE), a disease that was described in 1966 by Jellinek as a brain pathology with a vascular component and presence of anti-thyroid antibodies, which may be related to Hashimoto’s thyroiditis (TH). This disease can manifest itself in stroke-like episodes, psychiatric syndromes, and epileptic seizures in 66% of cases and does not have typical paraclinical features. Furthermore, it is drug resistant and involves a possible progression to partially complex, rarely generalized seizures, possibly followed by weakness. In this context, this article aims to verify the main pathophysiological and clinical repercussions of Hashimoto’s Encephalopathy from a bibliographical and exploratory study, using descriptors validated through Health Sciences Descriptors (DECS). It was found that there are factors related to the disease, such as genetic predominance, lack of chemical elements. Furthermore, studies have indicated that electroencephalographic and magnetic resonance imaging results are consistent in detecting Hashimoto’s encephalopathy.